A COMPARATIVE STUDY OF GIRL’S PHYSICAL SCIENCE PERFORMANCE BETWEEN CO-EDUCATIONAL AND SINGLE SEX SCHOOLS IN SWAZILAND - V. L , Kelly; O. I , Oloyede (International Journal of Research -GRANTHAALAYAH, 2019)
The major objective of the study was to compare the performance of girls studying physical science in single sex schools and those in co-educational schools. Three research questions were raised and one hypothesis formulated. The study adopted a cross-sectional survey research design using a sample of forty students’ randomly selected from two single – sex and two co – educational schools from the Manzini region of Swaziland. Data was collected using the Swaziland General Certificate of Secondary Examination results and a 10 – item 5 - scale Likert type of questionnaire. Data was analyzed using the Statistical Package for Social Sciences (SPSS). T-test was used to test the hypothesis at 0.05level of significance. The findings from this study showed that girls from single-sex schools perform significantly better in physical science than girls from co-educational schools. Social factors have the greatest influence on girl’s physical science performance, while school management issues have the least influence. It was concluded that performance of girls in single-sex schools is significantly different from the performance of girls from co-educational schools and social factors have the greatest influence on the physical science performance of girls. It was therefore recommended that teachers in co-educational school should do everything possible to improve the performance of girls in their schools and teachers in both schools should provide guidance and counseling services in order to educate the girls on the effects of social factors such as peer pressure on their physical science performance.